2012
DOI: 10.1371/journal.pone.0043412
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Alcohol Consumption and CYP 2C19 Gene Polymorphism in Relation to Oesophageal Squamous Cell Carcinoma

Abstract: ObjectivesThe purpose of this study is to explore the relationship between the interactions of CYP2C19 gene polymorphisms and several environmental factors and oesophageal squamous cell carcinoma (OSCC).MethodsIn a case-control study of OSCC patients (n = 350) and healthy controls (n = 350), we investigated the roles of polymorphism in the CYP2C19 gene by the use of polymerase chain reaction - restriction fragment length polymorphism (PCR – RFLP) analysis.ResultsThe CYP2C19*3 AG+AA genotype was significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
8
2
Order By: Relevance
“…CYP2C19*3 has a premature stop codon in exon 4 and it is biologically plausible that the CYP2C19*3 polymorphism is a modulator of cancer susceptibility; however, we did not find CYP2C19*3 to be associated with ESCC susceptibility in our study population. This finding is inconsistent with a recent report from Shi et al [ 27 ], who found that the frequency of the CYP2C19*3 A allele was significantly higher in ESCC patients than in controls (5.57% vs 1.86%, P = 0.004). Our current understanding of carcinogenesis indicates a multifactorial and multistep process involving various genetic alterations and environmental factors and it is unlikely that risk factors for cancer act in isolation from each other.…”
Section: Discussioncontrasting
confidence: 99%
“…CYP2C19*3 has a premature stop codon in exon 4 and it is biologically plausible that the CYP2C19*3 polymorphism is a modulator of cancer susceptibility; however, we did not find CYP2C19*3 to be associated with ESCC susceptibility in our study population. This finding is inconsistent with a recent report from Shi et al [ 27 ], who found that the frequency of the CYP2C19*3 A allele was significantly higher in ESCC patients than in controls (5.57% vs 1.86%, P = 0.004). Our current understanding of carcinogenesis indicates a multifactorial and multistep process involving various genetic alterations and environmental factors and it is unlikely that risk factors for cancer act in isolation from each other.…”
Section: Discussioncontrasting
confidence: 99%
“…The main study characteristics were summarized in Table 1 [20][36]. These studies indicate that the distribution of genotypes in controls was consistent with HWE.…”
Section: Resultsmentioning
confidence: 92%
“…A perfect NOS score is 9. In this meta-analysis, two studies scored 9 [18,19]; four studies scored 8 [20][21][22][23]; two studies scored 7 [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…In previous study, the result was inconsistent in CYP2C19*3 gene polymorphism. Wei et al found that there was no association between CYP2C19*3 gene polymorphism and ESCC risk in 2004 [22], whereas Yun et al reported that CYP2C19*3 gene A allele showed signi cantly more prevalent in ESCC patients in 2012 [19]. This meta-analysis combined the results of 6 associated studies and found that AA genotype of CYP2C19*3 polymorphism was related to ESCC risk (OR = 2.992, 95% CI = 1.122-7.981).…”
Section: Discussionmentioning
confidence: 99%